Economic costs of treating high blood pressure in the Adamaoua region of Cameroon - Zakariaou, Njoumemi; Djoulay-Hatou, (International Journal Of Community Medicine And Public Health, 2025)
Background: High blood pressure constitutes a major public health problem in Cameroon with a prevalence of 30.9% making it a major driver of healthcare costs. This study evaluated the economic cost of high blood pressure treatment in the Adamaoua region, in Cameroon. Methods: A cross-sectional medico-economic evaluation using the cost analysis was conducted. Costing approach used a bottom-up micro-costing with unit costs for diagnostic and therapeutic interventions and nonmedical and indirect costs. An average cost of treatment per patient was presented as mean, median and standard deviation. The linear regression was used to identify factors influencing the cost variations. The significance threshold was set at p˂5%. Results: A total number of 179 patients were sampled, including 112 patients with uncomplicated and 67 with complicated high blood pressure. The average annual total economic costs of uncomplicated high blood pressure to patients were estimated at XAF 220,276.76±75,743 (US$363.15±124.87) with the direct medical costs representing the highest proportion with (89.4%), following by the total indirect costs (7.3%), while the economic costs of treating complicated high blood pressure were estimated at XAF 346,516.05±292,081 (US$571.27±481.53) which mainly made up of direct medical costs (70.49%) followed by direct nonmedical cost (21.67%). Factors such as hospitalization, diet and transportation were statistically significant; while 33% of variability in expenses was related to hospitalization. Conclusions: The economic costs of uncomplicated and complicated high blood pressure imply the policy for eliminating the financial barriers by including the treatment of high blood pressure in the second phase of the universal health coverage.